2000
DOI: 10.1046/j.1360-0443.95.11s3.5.x
|View full text |Cite
|
Sign up to set email alerts
|

Truth or consequences: the validity of self‐report data in health services research on addictions

Abstract: This paper examines factors that influence the veracity of verbal self‐report data in health services research, using a cognitive social‐psychological model of the data‐gathering process as an organizing framework. It begins by briefly summarizing the consequences that can result from measurement error. Next, a cognitive social‐psychological model of the question‐answering process is presented. Common assumptions regarding the utility of specific assessment methods are evaluated with particular emphasis on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(60 citation statements)
references
References 0 publications
1
58
0
1
Order By: Relevance
“…Other limitations include the self-reported data used in this study, though the follow-up phone survey was conducted by an outside researcher, which increased the probability that participants would honestly disclose substance use and related consequences because it was confidential. In addition, previous research has found that substance users generally are reliable in self-reporting substance use (DelBoca & Noll, 2000). Also, participants were in a variety of treatment programs and there was no measure of ''dose'' of treatment in this study, so it was not possible to see how differences in treatment methods, length, hours, successful completion, or other characteristics such as provider skill or training might have impacted addiction severity outcomes for participants.…”
Section: Limitationsmentioning
confidence: 84%
“…Other limitations include the self-reported data used in this study, though the follow-up phone survey was conducted by an outside researcher, which increased the probability that participants would honestly disclose substance use and related consequences because it was confidential. In addition, previous research has found that substance users generally are reliable in self-reporting substance use (DelBoca & Noll, 2000). Also, participants were in a variety of treatment programs and there was no measure of ''dose'' of treatment in this study, so it was not possible to see how differences in treatment methods, length, hours, successful completion, or other characteristics such as provider skill or training might have impacted addiction severity outcomes for participants.…”
Section: Limitationsmentioning
confidence: 84%
“…In general, the rate of agreement about levels of abstinence increased over time, but the strength of agreement ranged from slight to fair except in the postpartum period when it was moderate (K=.48). Since self-report drinking data are neither inherently valid nor invalid, it cannot be assumed that either the self or partner report should be the gold standard, although some conventions increase the value of collateral information if it reveals more substance use than the self-report (Carey & Simons, 2000;DelBoca & Noll, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is often assessed using self-reports. This method has generally proven to be accurate if patients are alcohol free at the time of the assessment, although some experts see corroboration of the respondent's self-reports as desirable [23,24]. Combining self-reporting with biological indicators is also recommended [25].…”
Section: Outcome Assessmentmentioning
confidence: 99%